A casa corrente luso-brasileira em Minas Gerais: releitura sobre a casa urbana das regiões de Vila Rica e do Rio das Mortes (séculos XVIII e XIX) - Régis Eduardo Martins (2021)
This work proposes an investigation of Portuguese-Brazilian “common house”, from the 18t) and 19th centuries, in Minas Gerais, more specifically in the regions of former Vila Rica and Rio das Mortes. The “common house”, an almost unexplored classification in Brazil, can be considered one of the types of urban houses, which has covered, in our case, the production of a program architecture, replicated from solutions inaugurated in the urban reforms carried out by D. Manuel I, in Ribeira das Naus in Lisbon. In general, in Brazilian historiography, this theme was discussed in association of the preservation of cultural heritage, without being treated from a confrontation of the research object with the architecture of the same nature in Portugal. Thus, the objective is to propose a reinterpretation of colonial and imperial periods’ house, to reposition its analysis in the light of the research generated in Portuguese territory, intended for the treatment of the common house of the Middle and Modern ages. For that, it starts with a process of literature interpretation related to the theme in Brazil from the concept of representation, developed in cultural history. To understand the common house reproduction, the logic established by the notion of indicator paradigm is used to enable a parallel of the object manifestation in Portuguese Empire’s different contexts, thus, positioning the typologies identified in Minas Gerais on a scale of interconnected events and not independently, as many previous studies have objectified. With this, a scenario of reproduction of the object was identified, in the Modern Era, established according to the imperialist yearnings launched in Manueline reign, which the architecture played a strategic role of domination and control of its subjects. The symbolic dimension, emanating from this order imposition device, gave rise to a composition of standardized façades, based on architectural principles such as: repetition, rhythm, symmetry, order, harmony, etc. A non-natural fact in the reproduction of the vernacular architecture developed in Portugal, the diffusion of the aesthetic dimension introduced into Manueline interventions, from the beginning of the 16th century, demanded intense urban regulation and implementation efforts of architectural uniformity by the Casas de Câmara e Cadeia in the villages of Portuguese origin, all over the world. Therefore, the Portuguese-Brazilian “common house” widespread in Minas Gerais, in the chosen time frame, corresponded to a continuous effort made by Portuguese Crown, aimed to villages and cities beautification, and supported by the imposition of a program architecture, which reverberated to the last years of eight hundred, already incorporating to the façades some elements from architectural eclecticism in force at the time.